The Impact of the War on Human Capital and Productivity in Ukraine - Balázs Égert; Christine de la Maisonneuve (Center for Economic Studies and ifo Institute (CESifo), 2023)
In addition to the humanitarian suffering and huge immediate economic costs, the war in Ukraine will have long-term consequences, among which are losses in human capital that will impact aggregate productivity for many years. Exploiting a new stock measure of human capital combining the quality and quantity of education and adult skills, this paper suggests that losses in long-run aggregate productivity operating through the human capital channel could be at about 7% if the war lasts two years. These adverse effects come from school closure and the resulting decline in student learning outcomes and losses in workers' skills, which, without remedial policy action, could persist for decades.
Keywords: E24; I19; I20; I25; I26; I28; 330; human capital; productivity; educational achievement; student test score; adult test score; Ukraine